Education in Cambodia before Angkor Empire: Prehistory, Nokor Phnom, and Chenla Periods - Pisith Chin; Sereyrath Em; Sophea Phann; Sacha Seng (MASI Mandiri Edukasi, 2023)
Education is a fundamental human right that should be accessible to everyone, regardless of nationality or historical period. Education gives individuals the knowledge and skills necessary to succeed and contribute to society. It is essential for personal growth, development, and economic and social progress. Education promotes critical thinking, problem-solving, and creativity, crucial for innovation and progress. Besides, education is a vital component of human development and progress, and all individuals must have access to quality education regardless of their nationality or period in history. The importance of education is not an exception for Cambodia. Thus, this article reviews the aspects of education in the history of Cambodia before the Angkor period using different documents for consolations. As a result, some fascinating findings proved that people during the prehistoric period learned by watching and doing, and people mostly learned from religions during the Nokor Phnom and Chela periods of Cambodia. The article then concludes the mentioned aspects in a few sentences and the important recommendations.